Enhancing meaningful learning in MRSP120 rotational model - Othman, Suhaimi Zakaria (Serials Publications, 2016)
Studies on Blended Learning flourishingly have become main interest now in T&L approach. A lot of Model of Instruction venture on how to integrate technology with T&L especially involving Online Learning. In these studies, we will focus on Station Rotation Model which is one of the pedagogy approaches in delivering the content and inducing the Higher Order Thinking skill (HOTs) among the secondary student in Malaysia. Adoption and the hybridisation of this so call Blended Learning Model with Malaysian style of teaching were hoping critically assimilated the active learning environment in order to double up the generation thinking process among students. Meta-analysis on previous model will explain the component that will introduced to the newly enhanced Malaysian Instructional model which is called MRS120 Rotational Model. Theory on Meaningful Learning by Ausubel will be polished in this Model as discussed later in the paper.